COMPREHENSIVE HARDWARE AND SOFTWARE APPROACH TO DIGITALIZATION OF AGRICULTURAL INDUSTRY - Gulyaev Rinat Amirovich; Sultonov Azamat Akramovich; Ismoyilov Hayot Barotovich (Galaxy International Interdisciplinary Research Journal, 2021)
This article discusses the need for digitalization of the agroindustry, the regulatory framework, the possibilities of GIS systems in relation to the creation of hardware and software systems for digitalization and the existing systems used in the effective management of the agricultural sector.